The introduced signal crayfish and native noble crayfish have different effects on sublittoral macroinvertebrate assemblages in boreal lakes. (1st June 2015) - Ercoli, Fabio; Ruokonen, Timo J.; Koistinen, Sofia; Jones, Roger I.; Hämäläinen, Heikki
Summary We investigated differences in the abundance, community composition and taxon richness of sublittoral macroinvertebrates in boreal lakes containing introduced invasive signal crayfish (Pacifastacus leniusculus) or native noble crayfish (Astacus astacus). We hypothesised that sublittoral macroinvertebrate assemblages in lakes containing noble crayfish, which reportedly prefer the shallow littoral, would differ little from those in lakes without crayfish, in contrast to assemblages in lakes containing signal crayfish, which reportedly forage at greater depths. In a set of 24 small and medium‐sized Finnish lakes, eight lakes contained signal crayfish, eight had noble crayfish and eight control lakes had no crayfish. At three sites per lake, we sampled macroinvertebrates quantitatively from soft sediment in the sublittoral. The sublittoral macroinvertebrate assemblage in lakes with noble crayfish and control lakes was similar. In contrast, lakes with signal crayfish had a lower density of Trichoptera and Ephemeroptera, as well as a lower density and species richness of Chironomidae, and a lower overall benthic density and taxon richness. In contrast to some previous reports from other habitats, we infer that introduced signal crayfish have stronger negative effects than native noble crayfish on sublittoral macroinvertebrates. Hence, the ecological equivalence or differences of crayfish species cannot be generalised across habitats.